Retail Strategies to Support Healthy Eating - Alyssa Moran; Christina A. Roberto (MDPI, 2020)
In January 2020, the Center for Science in the Public Interest (CSPI), The Food Trust, Johns Hopkins Bloomberg School of Public Health, and Healthy Eating Research (HER) met for a Healthy Retail Research Convention in Washington, D.C. Attendees included food industry representatives, researchers, and nonprofit organizations. The objective of the convention was to develop a national healthy retail research agenda by (1) determining the effectiveness of government policies, corporate practices, and in-store pilots in promoting healthy eating; (2) identifying gaps in the healthy food retail literature and generating questions for future research, with an intentional focus on reducing health disparities and improving equity; (3) highlighting best practices for partnering with retailers and food manufacturers on healthy retail research; (4) facilitating relationships between retailers and researchers to implement and evaluate retail interventions; and (5) identifying existing datasets, ongoing work, and new opportunities for retail-research partnerships
Keywords: 330; trade promotion; price; promotion; placement; food and beverage; food retailer; grocery; consumer behavior; marketing; chronic disease; choice architecture; retail food environment; food purchasing; federal nutrition assistance; COVID-19; grocery stores; restaurants; dietary intake; food purchase; policy; federal nutrition assistance programs; beverage tax; menu labeling; financial incentives; health disparities; food access; nutrition; healthier food; dietary behaviors; review; grocery store; restaurant; environment; retail; food purchasing behavior; diet quality; diet disparities; urban; rural; socioeconomic; income disparities; consumer packaged goods; packaged foods; intersectionality; race; ethnicity; socioeconomic status; grocery retail; supermarket; research agenda; healthy food retail; food environment; online food retail; conceptual framework; food choices; online shopping; retailer policies